Comparison of single radial immunodiffusion, SDS-PAGE and HPLC potency assays for inactivated influenza vaccines shows differences in ability to predict immunogenicity of haemagglutinin antigen. Issue 29 (5th July 2018) - Engelhardt, Othmar G.; Edge, Chantal; Dunleavy, Una; Guilfoyle, Kate; Harvey, Ruth; Major, Diane; Newman, Robert; Penn, Rebecca; Skeldon, Sarah; Storey, Claire; Wheeler, Jun; Wood, John; et al.
Highlights: Two potential alternative influenza vaccine potency assays were compared with SRD. Forced degradation experiments showed differences between assays. Physico-chemical methods could not detect loss of potency as shown by SRD. Potency measured by physico-chemical methods did not correlate with immunogenicity. Abstract: The current gold-standard potency test for inactivated influenza vaccines is the single radial immunodiffusion (SRD) assay. A number of alternative potency tests for inactivated influenza vaccines have been proposed in recent years. Evaluation of these new potency tests commonly involves comparison with SRD, in order to ascertain that the new method obtains values that correlate with those measured by the standard potency test. Here, we extended comparison of two methods, reverse-phase HPLC and SDS-PAGE, with SRD by assessing the methods' capacity to detect loss of potency induced by various deliberate treatments of vaccine samples. We demonstrate that neither of these methods detected the loss of potency observed by SRD; importantly, neither SDS-PAGE nor reverse-phase HPLC reflected results from mouse experiments that showed decreased immunogenicity and protection in vivo. These results emphasise the importance of assessing the stability-indicating nature, ie the ability to measure loss of vaccine potency, of any potential new potency assay.